Sinonasal hemangiopericytoma: A rare case report with review of literature - Shobha, BV (J Oral Maxillofac Pathol, 2015)
Hemangiopericytoma (HPC) is a rare tumor of uncertain malignant potential. Stout and Murray described HPC as “vascular tumor arising from Zimmerman's pericyte” in 1942. The World Health Organization (WHO) reclassified HPC as a fibroblastic/myofibroblastic tumor, after further characterization. HPC is found mostly wherever there is increased vascularity seen. The incidence of the tumor in head and neck area is only 15%, mostly seen in adults. We report here a case of HPC of a 22-year-old female, who presented to our department with a tender swelling in maxillary anterior region and the mass was well-circumscribed, sessile and soft on palpation. The skin over the tumor was intact and normal. The tumor was completely removed with wide surgical resection. The histopathological staining supported the diagnosis of HPC, this was further confirmed by immunohistochemistry (IHC) in which CD99 showed strong positivity.